The transaction taxes in Turkey (1926-1934) :|negotiation between industrialists and republican governments - Demirkeser, Kerem. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2019., 2019)
This thesis investigates four taxes, which are the General Consumption Tax that was enacted in 1926 and three different Transaction Taxes that were enacted in 1927, 1931 and 1934; in addition, it focuses on the creation processes of these taxes and the negotiation between taxpayers and governments. In the existed structure of taxation after the abolition of the Âşar, tithe tax in 1925, these four taxes, which had vital share in the all tax revenues, constitutes the main headlines of this thesis and negotiations during creation processes of every single tax between taxpayers and taxpayers’ organizations such as chambers of commerce and industry unions and governments are examined. Also, the study investigates how taxpayers reacted against taxes; how they criticized the tax and which arguments were used; and which methods were developed in order to negotiate. Main sources of this thesis are necessary reasons texts, law texts and reports and documents that are written by chambers of commerce.
Keywords: Taxation -- Turkey.